Despair Beyond Repair? Severity of Hopelessness in Depressed Psychiatric Inpatients - C. Overholser James; Fisher Lauren; Braden Abby; Peak Nicole (Journal of Depression And Therapy, 2015)
Background: Depression is related to suicidal ideation, attempts, and completion. However, depression fails to provide any specific identification for suicide risk. Hopelessness has been found to provide a more accurate estimate of suicide risk than seen in depression severity, and hopelessness can serve as a useful predictor of eventual death by suicide. Aims: The present study was designed to examine various levels of hopelessness and their association with other symptoms experienced by depressed psychiatric inpatients. Method: 150 adult psychiatric inpatients were evaluated using a structured diagnostic interview and several standardized self-report questionnaires. All patients met criteria for a depressive diagnosis at the time of the evaluation. Patients were classified into four discrete categories of hopelessness using the Beck Hopelessness Scale. Results: No differences were observed when the four groups of depressed psychiatric inpatients were compared on demographic variables and background clinical events. However, several key differences were observed between groups on measures of depression severity, suicidal ideation, and tendencies to cope by distraction. Conclusions: It appears useful to evaluate suicide risk as it changes across different levels of hopelessness. Depressed patients with higher levels of hopelessness report more severe problems on several dimensions related to suicide risk.
Keywords: depression